Analisis Investasi Pengembangan dalam Hubungannya dengan Tingkat Pengembalian, Risiko, dan Sumber Pendanaan : Studi Kasus pada RS. Dr. H. Marzoeki Mahdi Bogor - Hidayat, Lukman; Widijawati, Eti (Jurnal Ilmiah Ranggagading (JIR), 2007)
In carrying out of this research, the reasearchers utilized descriptive method based on data collecting result such as finance accounting of a hospital that was studied. This descriptive method was intended to explain facts and population characteristic or certain things systematically, factually and accurately. Cash flow 2002 was Rp1.262.568.737, cash flow 2003 was Rp1.455.748.699, cash flow 2004 was rp1.461.743.838, and cash flow 2005 was Rp1.600.944.262. The increase of cash flow indicates that the hospital grows more and more. From the counting result of payback period, its found out that investment is good and return of investment percenrage is low. NPV gets close to zero, id est + Rp57.010.777 and - Rp5.426.050. It means that discount level of the hospital funding is between 35% - 36%, IRR (126%) > bank rate of interest (12%), so that fund of Rp3.497.085.485 that has been invested in the hospital produces 120%, far higher than bank rate of interst. Keywords: Investment analysis